The Influence of Crossfit on the Dynamics of Physical Fitness Indicators of Youth - Artur Oderov; Andrii Arabskyi; Yaroslav Pankevych; Svitlana Indyka; Natalia Bielikova; Viktor Lashta; Vasyl Antonets (Sport i Turystyka, 2024)
The strategy of modern higher education should form a specialist who is able not only to realize the accumulated potential of knowledge, abilities and skills, but also to go beyond the limits of regulated activities, which characterizes the tendency to increase the role of the “human factor” in all spheres of work, including in the military sphere. Therefore, the purpose of the research was to study and determine the effectiveness of the influence of CrossFit on the dynamics of indicators of physical fitness of young people. We conducted a comparative analysis of the level and dynamics of physical fitness of young people (17.6 ±0.2 years old; range: 17–21 years old), who during their studies, were systematically engaged in CrossFit activities (n = 24), and students who had PE classes run according to the existing program of physical education in higher education institutions (n = 23). The level of physical fitness was determined according to the results of exams andcredits in physical education. The study of the level of physical fitness of young people showed that the use of CrossFit leads to better resultsof basic physical qualities and positive changes in the human body (t = 4.44; p < 0.001).